Analisis kepatuhan wajib pajak berbasis gender bagi pelaku UMKM apotek di Jabodetabek - Ghea B Astrid; Haula Rosdiana (Keberlanjutan)
There has not been much research that analyzes the compliance of individual taxpayers of MSMEs of the pharmacy sector from a gender perspective. On the other hand, the pharmaceutical sector in the era of the Covid-19 pandemic was recorded as positively affected. Therefore, this initial research aims to describe the compliance of the Individual Taxpayers of the pharmacy business sector. With a population of 5,227 units in 2019, the sample was pharmacy owners in Jabodetabek, which with the formula Slovin, obtained a sample of 98.12 (rounded 100) with a convenience sampling technique. The inclusion criteria of the sample are pharmacies with a turnover of less than Rp: 4.8 billion a year and a sole proprietorship. Using the Mann-Whitney Test, the results revealed that although there was a higher trend of women, there was no significant difference in tax compliance based on the gender of individual taxpayers of MSMEs in the Pharmacy sector Jabodetabek. These results reinforce previous research stating no significant difference in tax compliance between men and women. This research can be an insight for tax authorities to pay attention to gender equality in improving compliance of the individual taxpayer of MSMEs in the pharmacy sector in Jabodetabek.